The Role Of E-Entrepreneurship in Achieving Sustainability in the Jordanian E-Business Environment - Al-Tubishat, Ali Mahmoud (Journal of Ecohumanism, 2024)
This study aimed to identify the role of e-entrepreneurship in achieving sustainability in the Jordanian e-business environment. The descriptive approach was used, and a questionnaire was designed to verify sustainability consisting of three areas. After ensuring its validity and reliability, it was distributed to the study sample consisting of (750) employees in Jordanian entrepreneurial companies, after collecting data and processing it statistically, it was found that there is a high and statistically significant role at the level of (0.05) in achieving environmental, social and economic sustainability, (R- Square) reached (0.749), (0.842) and (0.831) respectively, p=0.00, a set of recommendations were developed, the most prominent of which are work with the government to avoid risks that may occur in this field, work to improve the conditions of their workers, increase productivity and increase the rates of exporting their products abroad to participate in economic growth in Jordan and improve income rates.